Low-cost semantic enhancement to digital library metadata and indexing: Simple yet effective strategies - Hinze, Annika; Bainbridge, David; Cunningham, Sally Jo; Downie, J. Stephen (JCDL '16 : proceedings of the 16th ACM/IEEE-CS Joint Conference on Digital Libraries : June 19-23, 2016, Newark, NJ, USA, 2016)
Most existing digital libraries use traditional lexically-based retrieval techniques. For established systems, completely replacing, or even making significant changes to the document retrieval mechanism (document analysis, indexing strategy, query processing and query interface) would require major technological effort, and would most likely be disruptive. In this paper, we describe ways to use the results of semantic analysis and disambiguation, while retaining an existing keyword-based search and lexicographic index. We engineer this so the output of semantic analysis (performed off-line) is suitable for import directly into existing digital library metadata and index structures, and thus incorporated without the need for architecture modifications.